2019
DOI: 10.3390/agronomy9050220
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Tolerant Barley: II. Root Tip characteristics in Emerging Roots

Abstract: Reduced water resources are of increasingly urgent global concern. One potential strategy to address the crisis is the use of drought tolerant crops in agriculture. Barley varieties developed for reduced irrigation (“Solum” and “Solar”) use significantly less water than conventional varieties (“Cochise” and “Kopious”). The underlying mechanism of this drought tolerance is unknown but root structure and function play a key role in plant water uptake. In this study, an empirical survey compared early root develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…As mucilage plays important roles in maize water uptake under water stress (Ahmed et al 2018), it is therefore plausible that plant breeders in Kenya unintentionally selected for higher mucilage exudation, while selecting for drought resistance. Carter et al (2019) also indicated a higher mucilage exudation amount in a droughtresistant barley (Hordeum vulgare L.) compared to the drought-susceptible ones, suggesting a similar selection effect.…”
Section: Mucilage Exudation Rate Of Local Varieties Depends On Climat...mentioning
confidence: 72%
See 1 more Smart Citation
“…As mucilage plays important roles in maize water uptake under water stress (Ahmed et al 2018), it is therefore plausible that plant breeders in Kenya unintentionally selected for higher mucilage exudation, while selecting for drought resistance. Carter et al (2019) also indicated a higher mucilage exudation amount in a droughtresistant barley (Hordeum vulgare L.) compared to the drought-susceptible ones, suggesting a similar selection effect.…”
Section: Mucilage Exudation Rate Of Local Varieties Depends On Climat...mentioning
confidence: 72%
“…It was recently shown that the amount of nodal root mucilage exudation in the drought-resistant maize (Z. mays L.) varieties from India and Kenya were significantly higher than in those from Germany and France, being positively associated with the vapor pressure deficit of the varieties' agroecological zones of origin (Nazari et al 2020). Moreover, mucilage exudation was higher in a drought-resistant barley (Hordeum vulgare L.) variety than a conventional one (Carter et al 2019). These studies postulate that higher amounts of mucilage exudation have been unintentionally selected in the course of breeding under drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The functioning of connection gene hormones is related to germination response, which can be reduced under stress conditions (salt, drought) in sensitive barley cultivars (Emre et al, 2011;Thabet et al, 2018), and the physiological damage to the seed caused by stress can negatively affect seed viability and vigour, depending on genotype (Sun et al, 2007). In addition, the dynamic nature of root tip properties could have a significant impact on drought tolerance (Carter et al, 2019). Also, under salinity stress conditions, barley seed treatment with tryptophan and ascorbic acid as magneto-priming can improve seed germination (Hozayn and Ahmed, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nazari et al [ 40 ] studied the composition and quantity of mucilage exuded by maize from contrasting climatic regions and found that Indian and Kenyan genotypes from semi-arid regions secreted 135 and 125% more mucilage, respectively, compared to genotypes from central Europe. Similarly, India ink staining showed that root tips of drought-tolerant barley genotypes produced 1.2- to 1.5-times more mucilage than sensitive genotypes [ 39 ]. In addition, the secretion of mucilage provides both a biofilm-like environment and an accessible carbon source, which could help maintain beneficial microbial communities in the rhizosphere during a drought [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the mucilage acts as a hydraulic bridge between the roots and the soil, facilitating plant water uptake and maintaining transpiration in dry soils [ 6 ]. Most studies have focused on a range of grassland or crop species with different growth strategies [ 37 ], such as chickpea [ 38 ], barley [ 39 ], or maize [ 40 ].…”
Section: Introductionmentioning
confidence: 99%